The Impact of SIMCAR LASTRI Development on Team Communication in the Implementation of the Nursing Career Ladder at RSUD Tanjungpinang - Asmeriyanty, Asmeriyanty; Arif, Yulastri; Putri, Zifriyanti Minanda; Dorisnita (Rumah Sakit Umum Pusat (RSUP) Dr. M. Djamil, 2025)
Background: The implementation of a career ladder system in hospitals is crucial for the professional development of nurses. However, communication barriers within nursing teams often hinder the effectiveness of this system. SIMCAR LASTRI was developed to enhance communication within nursing teams, ensuring a more structured and efficient career progression process. This study aims to analyze the impact of SIMCAR LASTRI on team communication in the implementation of the nursing career ladder at RSUD Tanjungpinang. Methods: This study employed a quantitative analytical approach with a quasi-experimental design, involving 76 nursing practitioners at RSUD Tanjungpinang. Data were collected using structured questionnaires and analyzed using the Wilcoxon signed-rank test to assess the impact of SIMCAR LASTRI on team communication in career ladder implementation. Results: The univariate analysis revealed that the majority of respondents were female (92.1%), aged 26-35 years (73.7%), with a vocational education background (84.2%) and 7-15 years of work experience (54%). Before the implementation of SIMCAR LASTRI, 43.4% of nurses were at the Pre-PK level, and 61.84% of respondents perceived career ladder implementation as suboptimal, with major obstacles in the credentialing process (50%), competency assessment (36.84%), and issuance of Clinical Assignment Letters (SPK) and Clinical Authority Details (RKK) (34.21%). The analysis showed that before SIMCAR LASTRI implementation, the mean team communication score was 34.09 (median 34.00, range 30-37), which significantly increased to 41.88 (median 42.00, range 39-42) after implementation. Bivariate analysis confirmed a statistically significant positive impact of SIMCAR LASTRI on team communication, with a p-value of 0.000, indicating that its implementation facilitated better coordination, improved information flow, and enhanced clarity in career progression for nurses. Conclusion: These findings suggest that SIMCAR LASTRI plays a crucial role in improving communication within nursing teams, thereby optimizing the implementation of the career ladder system in hospitals. Further research is recommended to explore its long-term effects on job satisfaction, professional development, and healthcare service quality.